RESEARCH OF THE DEPLOYMENT OF TOOLS FOR DESIGN AND SIMULATIONS IN TECHNICAL EDUCATION - DVORAK, Karel (Journal of Technology and Information Education, 2012)
Increase of professional competencies of graduates of secondary schools and colleges of technical specialization is based on the educational methods and used didactic technologies. Knowledge of engineering issues is necessary to combine with the skills of using computer tools for design, simulations and preparation of a production technology. The presented text introduces the implementation and results of the research of mentioned application in education carried out among students of secondary schools and colleges. Research is focused on the increase of knowledge of engineering issues and skills of using engineering applications for solving of educational projects with the emphasis on the application of interdisciplinary relations of the field.
Keywords: design; interdisciplinary relations; project oriented education; simulations; engineering; virtual prototype.